Analisis Reduksi Emisi Gas Rumah Kaca Dari Pengelolaan Sampah Padat Di Kecamatan Marabahan Kabupaten Barito Kuala Provinsi Kalimantan Selatan - Ihsan Fahri; Ahmad Kurnain; Rizqi Putri Mahyudin; Yudi Ferrianta (EnviroScienteae, 2019)
This study analyzes the level and status of greenhouse gas emissions or removals from solid waste management activities in Marabahan Subdistrict, Formulates an action plan for solid waste management that is low in Greenhouse Gas emissions in Marabahan Subdistrict and Projects the level and status of emissions or Greenhouse Gas absorption from waste management solid in Marabahan District until 2030, according to the 2006 IPCC BAU scenario and mitigation actions. The waste sector greenhouse gas emissions inventory results in 2016 reached 5.16 Gg CO2-eq. However, due to improvements in domestic waste management, the 2016 greenhouse gas emissions rate was reduced by 11.1% compared to the BAU scenario. In 2016, waste sector greenhouse gas emissions in the BAU scenario are projected to reach 10.61 Gg CO2-eq, and will continue to grow until 2020 to 11.14 Gg CO2-eq, and in 2030 to 12.64 Gg CO2-eq. In Action Mitigation I waste management is carried out in the community by implementing methane recovery in the waste banks and TPS 3R. In Action Mitigation II, waste management is carried out at the Final Processing Site (TPA) carried out by the local government to handle it. When compared to the BAU scenario, the design of mitigation actions I and II in the context of reducing greenhouse gas emissions resulted in a decrease of 35.2%, 59.5% and 98.3% in 2013, 2020 and 2030.